AN ANALYSIS OF ENGLISH TEACHERS’ STRATEGIES IN TEACHING KELAS UNGGULAN AT ISLAMIC JUNIOR HIGH SCHOOL - Attabik, Muhammad Haikal (Universitas Bunda Mulia, 2024)
This study analyses English teachers’ strategies in teaching kelas unggulan, focusing on their implementation of various teaching strategies. The findings reveal that teachers use various teaching strategies, such as Direct Instruction, Cooperative Learning, Small Group Work, Problem-Solving, and Role-Play, but do not address the 21st-century teaching-learning approach of inquiry, discovery, critical thinking, communication skills, creativity, and digital literacy. Internal and external inhibiting factors, such as a shortage of training, limited mastery of teaching strategies, lack of professional development, and unfamiliarity with education technology, hinder teachers’ ability to apply these strategies effectively. To overcome these challenges, teachers seek random teaching strategies, participate in training outside of school, and collaborate with teachers who understand education technology. Internal factors include teacher confusion about students’ unreadiness and a lack of pedagogical competence. External factors include students’ lack of English proficiency, which can be addressed through practice time, vocabulary memorization, and repetition. However, these methods are no longer compatible with 21st-century learning requirements. The study suggests that the concept of kelas unggulan should be reconsidered, and a new investment in teacher professional development is urgently needed.